The Role of Equivalence-Based Procedures in Establishing Knowledge of Carbohydrate Content in Food Items - Arntzen, Erik; Spilling, Ina Charlotte (Perspectivas em Análise do Comportamento, 2026)
The study aimed to train participants on the carbohydrate values of various food items and evaluate the effect over a three-week period. Twenty-seven participants were assigned to three different groups. Groups 1 and 2 aimed to establish three-member classes, while Group 3 aimed for five-member classes. Initially, participants pre-sorted cards labeled with food items in categories based on the amount of carbohydrates: “less than 20,” “20–40,” and “more than 40” grams per 100 grams. Additionally, participants in Groups 2 and 3 could sort items into a “don’t know” category. Any incorrectly sorted items were identified and customized for each participant. Thus, tailored stimuli, incorrectly sorted stimuli, were then used for each participant in Many-to-One conditional discrimination training. Maintenance of the learned categories was tested after one week. Participants who did not meet the mastery criterion received additional training and testing. A second test of maintenance was conducted after three weeks. Both tests included tests for equivalence class formation in MTS and sorting format. The results showed that most participants responded correctly in both test formats. The majority of participants maintained the equivalence classes across all groups over the three-week period.